1984
DOI: 10.1002/cne.902270106
|View full text |Cite
|
Sign up to set email alerts
|

Olivary projections from the mesodiencephalic structures in the cat studied by means of axonal transport of horseradish peroxidase and tritiated amino acids

Abstract: By means of horseradish peroxidase (HRP) and autoradiographic methods, olivary projections from mesodiencephalic structures were studied in the cat. Following HRP injections in various parts of the inferior olive, many cells were labeled ipsilaterally in the nucleus of Darkschewitsch, the nucleus accessorius medialis of Bechterew, the nucleus of the fields of Forel, and the subnucleus dorsomedialis and ventrolateralis of the parvocellular red nucleus. Some labeled cells also occurred ipsilaterally in the supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 32 publications
9
72
0
Order By: Relevance
“…These descending axons presumably are destined for targets in the posterior brainstem and/or spinal cord. Neurons in the region of the field H of Forel, including the riMLF, have descending efferent projections to the lower brainstem, including the pontomedullary reticular formation (nucleus reticularis pontis caudalis and nucleus reticularis gigantocellularis; Isa et al, 1988b;Isa and Itouji, 1992;Isa and Sasaki, 1992a;Shiraishi and Nakao, 19941, the inferior olivary nucleus Courville, 1981, 1982;Onodera, 1984;Spence and SaintCyr, 1988a;Isa and Sasaki, 1992a), and the vestibular complex (Spence and Saint-Cyr, 1988a,b;Isa and Sasaki, 1992a). The riMLF and, more generally, the field H of Forel also project to the cervical spinal cord (Isa et al, 1988a,b;Holstege, 1988;Spence and Saint-Cyr, 1988a;Holstege and Cowie, 1989;Isa and Itouji, 1992;Isa and Sasaki, 1992a,b;Robinson et al, 1994), specifically targeting biventer cervicis and complexus motoneurons that are related to head movement (Isa et al, 1988a;Isa and Sasaki, 199213).…”
Section: A-p Stereotaxic Coordinatementioning
confidence: 99%
“…These descending axons presumably are destined for targets in the posterior brainstem and/or spinal cord. Neurons in the region of the field H of Forel, including the riMLF, have descending efferent projections to the lower brainstem, including the pontomedullary reticular formation (nucleus reticularis pontis caudalis and nucleus reticularis gigantocellularis; Isa et al, 1988b;Isa and Itouji, 1992;Isa and Sasaki, 1992a;Shiraishi and Nakao, 19941, the inferior olivary nucleus Courville, 1981, 1982;Onodera, 1984;Spence and SaintCyr, 1988a;Isa and Sasaki, 1992a), and the vestibular complex (Spence and Saint-Cyr, 1988a,b;Isa and Sasaki, 1992a). The riMLF and, more generally, the field H of Forel also project to the cervical spinal cord (Isa et al, 1988a,b;Holstege, 1988;Spence and Saint-Cyr, 1988a;Holstege and Cowie, 1989;Isa and Itouji, 1992;Isa and Sasaki, 1992a,b;Robinson et al, 1994), specifically targeting biventer cervicis and complexus motoneurons that are related to head movement (Isa et al, 1988a;Isa and Sasaki, 199213).…”
Section: A-p Stereotaxic Coordinatementioning
confidence: 99%
“…8 B). In group I, the v-PO, d-PO, r-MAO, and subnucleus a receive input from the cerebral cortex relayed by nuclei in the mesodiencephalic junction (Swenson and Castro, 1983;Onodera, 1984;Holstege and Tan, 1988;de Zeeuw, 1989) (Fig. 8 B, green arrows), although the subnucleus a also receive input from the spinal cord (Matsushita et al, 1991).…”
Section: Organization Of the Inferior Olive: Five Groups Related To Dmentioning
confidence: 99%
“…Concerning group III, the subnucleus b of the MAO receives heterogeneous input from the spinal cord and dorsal column nuclei with crude somatotopy (Boesten and Voogd, 1975;Berkley and Hand, 1978;Matsushita et al, 1992;Molinari et al, 1996) and from the vestibular nuclei and the mesodiencephalic junction (Swenson and Castro, 1983;Onodera, 1984;Gerrits et al, 1985) ( Fig. 8 B, ocher arrow).…”
Section: Organization Of the Inferior Olive: Five Groups Related To Dmentioning
confidence: 99%
“…1984] while the ND efferent outputs had their major target field in the medial accessory olive [Saint-Cyr and Courville. 1982;Onodera, 1984], More recently, in the cat afferent projec tions from the pericruciate cortex and the deep cerebellar nuclei were demonstrated as ending inside the ND over lapping in areas of the ND which in turn projected back to the cortex. It was thus suggested that the ND played an integrative role in these circuits [Rutherford et al.…”
Section: Discussionmentioning
confidence: 99%